(untitled) (Political Science Journal, 2025)
Public Enterprises (PEs) were established globally after 1930 with the goal of accelerating national economic growth. These entities were seen as key drivers of socio-economic development across different political systems. However, by the late 1970s, the financial and operational inefficiencies of PEs led to an increased economic burden on public funds. In the early 1980s, a new concept emerged globally aimed at economic reforms, known as economic liberalization, open market policies, and globalization. Privatization became a key tool for implementing this concept, with the objective of transferring public sector authority to the private sector to improve the financial and operational performance of PEs. Since 1992, the government of Nepal has followed this global trend, privatizing 30 PEs by 2020. Of these, 22 PEs were privatized through methods such as share sales and liquidation, while the remaining ones were privatized through business sales, management contracts, or dissolution. Among the privatized PEs, 11 are still operational, with 8 having been privatized via the share sale method. Between 1992 and 1996, as well as 2002 to 2006, a significant portion of PEs were privatized. However, privatization efforts have slowed down after 2008. This analysis is based on secondary data, and the findings are presented using percentage calculations.